Positive electrode active material and preparation method thereof, positive plate and battery

By coating the outside of the lithium manganese iron phosphate material with a shell of carbon and nitrogen elements to form a core and shell composite structure, the problems of poor conductivity and Mn ion dissolution of the lithium manganese iron phosphate battery are solved, and high stability and high efficiency operation of the battery are achieved.

CN120784306APending Publication Date: 2025-10-14TIANJIN RONBAY SKYLAND TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510845410.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

The electron and ion conductivity of lithium manganese iron phosphate batteries is poor, resulting in increased resistance, and Mn ions are easily dissolved, affecting the battery capacity, first charge efficiency and capacity retention rate.

Method used

A carbon layer and a nitrogen shell are coated on the outside of the lithium manganese iron phosphate material to form a composite structure of core and shell. The core is LiMn1-x-yFexMyPO4 and the shell is carbon and nitrogen elements. By controlling the element content and structure, the lattice structure of the positive electrode active material is stabilized, Mn dissolution is reduced, and a conductive network is constructed.

Benefits of technology

The electronic and ionic conductivity of the positive electrode active material is improved, the impedance of the battery is reduced, and the battery capacity, first charge efficiency and capacity retention rate are increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a positive active material and a preparation method thereof, a positive plate and a battery. The positive electrode active material comprises an inner core and a shell layer coating at least part of the surface of the inner core; the inner core comprises LiMn < 1-x > FexMyPO4; wherein 1-x is greater than 0; x > 0; y > 0; the M element comprises one or more of Mg, Ca, Sr, Co, Ti, Zr, Ni, Cr and Zn; the shell layer comprises a carbon element and a nitrogen element. The positive electrode active material provided by the embodiment of the invention has relatively good electron and ion conductivity, can stabilize Mn ions in the positive electrode active material, and is beneficial to reducing impedance of a battery and improving capacity, initial charging efficiency and capacity retention rate of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of batteries, in particular to a positive electrode active material, a preparation method thereof, a positive electrode sheet and a battery. BACKGROUND

[0002] Lithium ion batteries are widely used in mobile devices, electric vehicles, energy storage systems and other fields due to their high energy density and sustainability. Among them, lithium manganese iron phosphate batteries are attracting attention due to their high energy density.

[0003] However, the poor electronic and ionic conductivity of lithium manganese iron phosphate materials leads to an increase in the resistance of the battery, and the Mn ions are easily dissolved due to the Jahn-Teller effect, which reduces the capacity, the first charge efficiency and the capacity retention rate of the battery.

[0004] Therefore, there is an urgent need for a lithium manganese iron phosphate positive electrode active material that has good electronic and ionic conductivity and high stability, which is beneficial to reduce the impedance of the battery and improve the capacity, the first charge efficiency and the capacity retention rate of the battery. SUMMARY

[0005] The embodiments of the present application provide a positive electrode active material, a preparation method thereof, a positive electrode sheet and a battery. The positive electrode active material has good electronic and ionic conductivity and can stabilize the Mn ions in the positive electrode active material, which is beneficial to reduce the impedance of the battery and improve the capacity, the first charge efficiency and the capacity retention rate of the battery.

[0006] The embodiments of the present application provide a positive electrode active material, which comprises a core and a shell layer coated on at least part of the surface of the core.

[0007] The core comprises LiMn 1-x Fe x M y PO4;

[0008] wherein 1-x>0;

[0009] x>0;

[0010] y>0;

[0011] The M element comprises one or more elements selected from Mg, Ca, Sr, Co, Ti, Zr, Ni, Cr and Zn

[0012] The shell layer comprises carbon elements and nitrogen elements.

[0013] In some embodiments of the present application, the positive electrode active material has a resistivity of 10Ω·cm to 100Ω·cm.

[0014] In some embodiments of the present application, in the core, 0.2≤x≤0.7;

[0015] And / or, 0

[0016] In some embodiments of the present application, the particle size of the positive electrode active material is 0.2 μm-0.6 μm;

[0017] And / or, the thickness of the shell layer is 1 nm-5 nm;

[0018] And / or, the number ratio of nitrogen atoms to carbon atoms in the shell layer is 0.01 at%-0.1 at%.

[0019] In some embodiments of the present application, the positive electrode active material is prepared using a method comprising the following steps:

[0020] The raw materials including lithium source, manganese source, iron source, phosphorus source, M source, carbon source and nitrogen source are sequentially subjected to hydrothermal reaction and sintering treatment to obtain the positive electrode active material.

[0021] The present application further provides a preparation method of the positive electrode active material as described above, comprising the following steps:

[0022] The raw materials including lithium source, manganese source, iron source, phosphorus source, M source, carbon source and nitrogen source are sequentially subjected to hydrothermal reaction and sintering treatment to obtain the positive electrode active material.

[0023] In some embodiments of the present application, before the hydrothermal reaction, at least one of a template control agent and an organic dispersing agent is added to the raw materials, and then the hydrothermal reaction is performed;

[0024] The template control agent includes one or more of polyaniline, dopamine, polystyrene and polyvinyl alcohol;

[0025] And / or, the organic dispersing agent includes one or more of ethylene glycol, diethylene glycol, glycerol and polyethylene glycol;

[0026] And / or, the mass ratio of the template control agent to the carbon source is (0.5-2.5):1.

[0027] And / or, the phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, sodium phosphate and sodium dihydrogen phosphate;

[0028] And / or, the manganese source includes one or more of manganese oxalate, manganese carbonate, manganese sulfate and manganese acetate;

[0029] And / or, the iron source includes one or more of iron oxalate, iron nitrate and iron sulfate;

[0030] And / or, the lithium source comprises one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium oxalate;

[0031] And / or, the carbon source comprises one or more of graphene, carbon nanotube, glucose, starch, ascorbic acid, polyethylene glycol;

[0032] And / or, the nitrogen source comprises one or more of urea, imidazole, polyaniline.

[0033] In some embodiments of the present application, the heating rate of the hydrothermal reaction is 2℃ / min ~ 20℃ / min; preferably, the heating rate of the hydrothermal reaction is 5℃ / min ~ 15℃ / min;

[0034] And / or, the reaction temperature of the hydrothermal reaction is 100℃ ~ 200℃; preferably, the reaction temperature of the hydrothermal reaction is 150℃ ~ 190℃;

[0035] And / or, the reaction time of the hydrothermal reaction is 3h ~ 10h; preferably, the reaction time of the hydrothermal reaction is 4h ~ 7h;

[0036] And / or, the heating rate of the sintering treatment is 1℃ / min ~ 10℃ / min; preferably, the heating rate of the sintering treatment is 3℃ / min ~ 6℃ / min;

[0037] And / or, the reaction temperature of the sintering treatment is 500℃ ~ 750℃; preferably, the reaction temperature of the sintering treatment is 600℃ ~ 750℃;

[0038] And / or, the reaction time of the sintering treatment is 1h ~ 6h; preferably, the reaction time of the sintering treatment is 2h ~ 4h.

[0039] The present application also provides a positive electrode sheet, which comprises a positive electrode active layer, and the positive electrode active layer comprises the positive electrode active material as described above or is prepared by the preparation method of the positive electrode active material as described above.

[0040] The present application also provides a battery, which comprises the positive electrode sheet as described above.

[0041] The positive electrode active material, the preparation method thereof, the positive electrode sheet and the battery provided by the embodiments of the present application, the positive electrode active material comprises a core and a shell layer coated on at least part of the surface of the core, the core is doped with a special element, and the shell layer comprises carbon elements and nitrogen elements, so that the positive electrode active material has higher ion and electron conductivity and higher stability during the operation of the battery, thereby reducing the impedance of the battery and improving the capacity, the first charge efficiency and the capacity retention rate of the battery. DETAILED DESCRIPTION

[0042] In order to make the objects, technical solutions and advantages of the present application clearer, the following will be combined with the embodiments of the present application to make a clear and complete description of the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.

[0043] The lithium iron manganese phosphate battery has high energy density, but its ion conductivity and stability are poor, which leads to increased internal resistance and limits its application in batteries.

[0044] The inventor has found through research that coating a carbon layer on the outside of a traditional lithium iron manganese phosphate material can improve the stability of the lithium iron manganese phosphate positive electrode active material and reduce the dissolution of Mn ions, but there is an interface between the coating layer and the core, and the interface effect caused by the interface can reduce the ion conductivity of the lithium iron manganese phosphate positive electrode active material, which in turn leads to increased internal resistance and is not conducive to the normal operation of the battery.

[0045] Therefore, there is an urgent need for a lithium iron manganese phosphate positive electrode active material that balances stability and low internal resistance.

[0046] Based on this, the embodiments of the present application provide a positive electrode active material, which comprises a core and a shell layer coated on at least part of the surface of the core; the core comprises LiMn 1-x-y Fe x M y PO4; wherein 1-x>0; x>0; y>0; the M element comprises one or more elements selected from Mg, Ca, Sr, Co, Ti, Zr, Ni, Cr and Zn; and the shell layer comprises nitrogen and carbon elements.

[0047] The positive electrode active material of the embodiments of the present application has high ion and electron conductivity and high stability, which is conducive to reducing the impedance of the battery and improving the capacity, first charge efficiency and capacity retention rate of the battery.

[0048] In detail, the positive electrode active material of the embodiments of the present application is in a spherical or spherical-like structure. The shell layer can be coated on part of the surface of the core of the positive electrode active material or on the entire surface of the core of the positive electrode active material.

[0049] It should be noted that the inner core of the positive electrode active material in the embodiment of the present application comprises Li elements, Mn elements, Fe elements, M elements, P elements, and the above elements form lithium manganese iron phosphate crystals, and the lithium manganese iron phosphate crystals are the main components of the inner core of the positive electrode active material. In addition, a small amount of carbon elements and nitrogen elements exist on the surface of the lithium manganese iron phosphate crystals and between the lithium manganese iron phosphate crystals, which is beneficial to improve the ion and electron conductivity of the positive electrode active material. Specifically, the shell is grown on at least part of the surface of the inner core, that is, there is no interface effect between the shell and the inner core, which is beneficial to reduce the internal resistance of the positive electrode active material. In the positive electrode active material of the embodiment of the present application, by doping M elements in the conventional lithium manganese iron phosphate material and controlling the content of the above elements, the crystal lattice structure of the positive electrode active material can be stabilized, and the Mn dissolution can be reduced. When the inner core has the above composition, a rich conductive network is also constructed inside the positive electrode active material; at the same time, the shell has more nitrogen elements and carbon elements, which further stabilizes the stability of the positive electrode active material without affecting the ion and electron conductivity of the positive electrode active material. Therefore, the stability and ion and electron conductivity of the positive electrode active material of the embodiment of the present application can be improved, which is beneficial to reduce the impedance of the battery and improve the capacity, the first charge efficiency and the capacity retention rate of the battery.

[0050] In some specific embodiments, the structure and composition of the positive electrode active material can be detected by conventional methods and instruments. For example, the structure of the positive electrode active material can be characterized by using SEM and XRD; and the composition of each element in the positive electrode active material can be detected by using ICP.

[0051] In some embodiments of the present application, the resistivity of the positive electrode active material is 10Ω·cm-100Ω·cm. When the positive electrode active material of the embodiment of the present application has the above composition and structure, the ion conductivity of the positive electrode active material can be better improved, which is beneficial to better reduce the impedance of the battery. The resistivity of the positive electrode active material of the embodiment of the present application can be detected by conventional test methods and instruments. Specifically, the resistivity of the positive electrode active material can be measured by a powder resistivity tester, for example.

[0052] The inventors have found that by further controlling the element composition of the positive electrode active material, the ion and electron conductivity of the positive electrode active material can be more effectively improved, and the internal resistance of the positive electrode active material can be reduced.

[0053] In some embodiments, when 0.2≤x≤0.7, it is beneficial to better reduce the impedance of the battery and better improve the capacity, the first charge efficiency and the capacity retention rate of the battery.

[0054] In some embodiments, 0 < y < 0.02, which is conducive to better reducing the impedance of the battery and better improving the capacity, the first charge efficiency, and the capacity retention rate of the battery.

[0055] In some embodiments of the present application, the particle size of the positive electrode active material is 0.2-0.6 μm, which can better improve the ion and electron conductivity of the positive electrode active material, accelerate the conduction rate of lithium ions, and further improve the problem of side reactions between the positive electrode active material and the electrolyte, and better improve the impedance, capacity, first charge efficiency, and capacity retention rate of the battery. For example, the particle size of the positive electrode active material is 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, or a range consisting of any two of them. In the embodiments of the present application, the particle size of the positive electrode active material can be detected using conventional test methods and instruments. In a specific implementation, the particle size of the positive electrode active material can be measured using SEM.

[0056] In some embodiments, the thickness of the shell layer of the positive electrode active material is 1-5 nm, which can further improve the stability and internal resistance of the positive electrode active material, and is conducive to better reducing the impedance of the battery and better improving the capacity, the first charge efficiency, and the capacity retention rate of the battery. For example, the thickness of the shell layer of the positive electrode active material is 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, or a range consisting of any two of them. In the embodiments of the present application, the thickness of the shell layer of the positive electrode active material can be detected by conventional test methods and instruments. In a specific implementation, the thickness of the shell layer of the positive electrode active material can be measured by TEM after imaging.

[0057] The inventors have found that by controlling the number ratio of nitrogen atoms to carbon atoms in the shell layer, the electronic and ionic conductivity and stability of the positive electrode active material can be better improved, the impedance of the battery can be better reduced, and the capacity, the first charge efficiency, and the capacity retention rate of the battery can be further improved. In some embodiments, the number ratio of nitrogen atoms to carbon atoms in the shell layer is 0.01 at%-0.1 at%. For example, the number ratio of nitrogen atoms to carbon atoms in the shell layer is 0.01 at%, 0.02 at%, 0.04 at%, 0.06 at%, 0.08 at%, 0.1 at%, or a range consisting of any two of them.

[0058] In the embodiment of the present application, the positive electrode active material is prepared by using a method comprising the following steps: sequentially performing hydrothermal reaction and sintering treatment on raw materials comprising a lithium source, a manganese source, an iron source, a phosphorus source, an M source, a carbon source and a nitrogen source to obtain the positive electrode active material. By using the above preparation method, the positive electrode active material with continuous distribution between the core and the shell (i.e. the shell grows on at least part of the surface of the core) can be prepared, which is beneficial to better improve the stability and internal resistance of the positive electrode active material, and thus is beneficial to better reduce the impedance of the battery and better improve the capacity, the first charge efficiency and the capacity retention rate of the battery.

[0059] The embodiment of the present application also provides a preparation method of a positive electrode active material, comprising the following steps: sequentially performing hydrothermal reaction and sintering treatment on raw materials comprising a lithium source, a manganese source, an iron source, a phosphorus source, an M source, a carbon source and a nitrogen source to obtain the positive electrode active material.

[0060] By using the above preparation method of the positive electrode active material, the positive electrode active material with the special composition and structure can be prepared, and the positive electrode active material has higher stability and lower internal resistance, and can better reduce the impedance of the battery and better improve the capacity, the first charge efficiency and the capacity retention rate of the battery.

[0061] It should be noted that, in the embodiment of the present application, the feeding ratio of the lithium source, the manganese source, the iron source, the phosphorus source, the M source, the carbon source and the nitrogen source can be controlled according to the demand for the positive electrode active material to prepare the target product.

[0062] In some embodiments of the present application, the raw materials comprising the lithium source, the manganese source, the iron source, the phosphorus source, the M source, the carbon source and the nitrogen source are dissolved in a solvent to form a mixed solution for subsequent reaction. The present application does not specially limit the ratio of the raw materials and the solvent, which can be selected according to the actual situation. The present application also does not specially limit the type of the solvent, which can be selected according to the actual situation. For example, the solvent can be water.

[0063] In some embodiments of the present application, the molar ratio of the lithium source to the phosphorus source can be (2.7-3.2):1, and the molar ratio of the iron source to the manganese source can be 0.2:0.8-0.7:0.3; and the total mass ratio of the lithium source, the phosphorus source, the manganese source, the iron source, the carbon source, the nitrogen source and the template control agent to the mass of water can be (0.5-2):1.

[0064] In order to make the above raw materials more uniformly mixed, the above mixed solution can be subjected to ultrasonic stirring, and the temperature and time of the ultrasonic stirring are not specially limited in the embodiment of the present application, which can be selected according to the actual situation.

[0065] Based on the consideration of improving the purity of the positive electrode active material, inert gas or nitrogen can also be introduced in the hydrothermal reaction and the calcination reaction.

[0066] In some embodiments, the hydrothermal reaction can be performed in a stirred hydrothermal reactor.

[0067] In some embodiments, the hydrothermal reaction further comprises adding at least one of a template control agent and an organic dispersing agent to the raw materials before the hydrothermal reaction. In detail, the template control agent can make the particle size of the positive electrode active material about 0.2 μm to 0.6 μm by better inhibiting particle agglomeration, better improve the ion and electron conductivity of the positive electrode active material, accelerate the conduction rate of lithium ions, and further improve the problem of side reactions between the positive electrode active material and the electrolyte, and better improve the impedance, capacity, first charge efficiency, and capacity retention rate of the battery. In addition, the template control agent can provide a nitrogen source for the positive electrode active material, further improving the ion and electron conductivity of the positive electrode active material.

[0068] The organic dispersing agent can make the components in the raw materials fully dispersed, more conducive to forming the positive electrode active material with the above structure and composition, further reduce the stability and internal resistance of the positive electrode active material, and better improve the capacity, first charge efficiency, and capacity retention rate of the battery, and better reduce the impedance of the battery. The amount of the template control agent and the organic dispersing agent is not specially limited in the embodiments of the present application, and can be selected according to actual needs. For example, the mass ratio of the solvent to the organic dispersing agent can be (0.2-1):1.

[0069] In some embodiments of the present application, the hydrothermal reaction further comprises cooling the product of the hydrothermal reaction, solid-liquid separation after cooling, and grinding and sieving the dried product. The rotation speed and time of grinding are not specially limited in the embodiments of the present application, and can be selected according to actual conditions. For example, the product after cooling can be subjected to solid-liquid separation by a centrifuge, then the solid components are washed with deionized water for 3 times, and then the washed product is vacuum dried at 40-100°C for 6-24h, to obtain a sub-micro positive electrode active material. The sub-micro positive electrode active material is ground and sieved through a 200-mesh sieve, and then subjected to subsequent sintering treatment.

[0070] In some embodiments, the template control agent comprises one or more of polyaniline, dopamine, polystyrene, and polyvinyl alcohol, which have better particle size control effect, better improve the ion and electron conductivity of the positive electrode active material, and further better improve the capacity, first charge efficiency, and capacity retention rate of the battery. It should be noted that when the template control agent comprises at least one of polyaniline and dopamine, it can also provide a nitrogen source for the positive electrode active material, so that the shell layer of the positive electrode active material has sufficient nitrogen element doping, which is conducive to better improving the ion and electron conductivity and stability of the positive electrode active material.

[0071] In some embodiments, the organic dispersant comprises one or more of ethylene glycol, diethylene glycol, glycerol, polyethylene glycol, which have better dispersing effect, so that the stability and internal resistance of the positive active material are further reduced, and the capacity, first charge efficiency, capacity retention rate of the battery are better improved, and the impedance of the battery is better reduced.

[0072] In some embodiments, when the mass ratio of the template control agent to the carbon source is (0.5-2.5):1, the ion and electron conductivity of the positive active material can be better improved, and the capacity, first charge efficiency, capacity retention rate of the battery are better improved.

[0073] The embodiments of the present application further take into account the improvement of the stability and internal resistance of the positive active material by controlling the source of raw materials.

[0074] In some embodiments, the phosphorus source comprises one or more of phosphoric acid, ammonium dihydrogen phosphate, sodium phosphate, sodium dihydrogen phosphate.

[0075] In some embodiments, the manganese source comprises one or more of manganese oxalate, manganese carbonate, manganese sulfate, manganese acetate.

[0076] In some embodiments, the iron source comprises one or more of iron oxalate, iron nitrate, iron sulfate.

[0077] In some embodiments, the lithium source comprises one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium oxalate.

[0078] In some embodiments, the carbon source comprises one or more of graphene, carbon nanotube, glucose, starch, ascorbic acid, polyethylene glycol (PEG).

[0079] In some embodiments, the nitrogen source comprises one or more of urea, imidazole, polyaniline.

[0080] The inventors have found that by controlling the reaction conditions of the hydrothermal reaction and the sintering process, the stability and internal resistance of the positive active material can be better improved, the impedance of the battery can be better reduced, and the capacity, first charge efficiency, capacity retention rate of the battery can be better improved.

[0081] In some embodiments, the heating rate of the hydrothermal reaction is 2℃ / min-20℃ / min, for example, the heating rate of the hydrothermal reaction is, for example, 2℃ / min, 5℃ / min, 10℃ / min, 15℃ / min, 20℃ / min or a range formed by any two of them. Preferably, the heating rate of the hydrothermal reaction is 5℃ / min-15℃ / min.

[0082] In some embodiments, the reaction temperature of the hydrothermal reaction is 100-200℃, for example, the reaction temperature of the hydrothermal reaction is, for example, 150℃, 160℃, 170℃, 180℃, 190℃, or a range defined by any two of them. Preferably, the reaction temperature of the hydrothermal reaction is 150-190℃.

[0083] In some embodiments, the reaction time of the hydrothermal reaction is 3-10h, for example, the reaction time of the hydrothermal reaction is, for example, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or a range defined by any two of them. Preferably, the reaction time of the hydrothermal reaction is 4-7h. It should be noted that the reaction time of the hydrothermal reaction described above refers to the holding time after heating to the preset reaction temperature.

[0084] In some embodiments, the heating rate of the sintering treatment is 1-10℃ / min, for example, the heating rate of the sintering treatment is, for example, 1℃ / min, 3℃ / min, 5℃ / min, 8℃ / min, 10℃ / min, or a range defined by any two of them. Preferably, the heating rate of the sintering treatment is 3-6℃ / min.

[0085] In some embodiments, the reaction temperature of the sintering treatment is 500-750℃, for example, the reaction temperature of the sintering treatment is, for example, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, or a range defined by any two of them. Preferably, the reaction temperature of the sintering treatment is 600-750℃.

[0086] In some embodiments, the reaction time of the sintering treatment is 1-6h, for example, the reaction time of the sintering treatment is, for example, 1h, 2h, 3h, 4h, 5h, 6h, or a range defined by any two of them. Preferably, the reaction time of the sintering treatment is 2-4h. It should be noted that the reaction time of the sintering treatment is the holding time after heating to the preset reaction temperature of the sintering treatment.

[0087] The embodiment of the present application also provides a positive electrode sheet, which comprises a positive electrode active layer, and the positive electrode active layer comprises the positive electrode active material described above. The positive electrode sheet has the advantages corresponding to the positive electrode active material described above, which will not be repeated here.

[0088] The embodiment of the present application also provides a battery comprising the battery element described above. The battery provided by the present application has the advantages corresponding to the positive electrode active material described above, which will not be repeated here.

[0089] The battery of the embodiment of the present application can be a lithium ion battery (such as a lithium ion power battery).

[0090] Generally, the battery includes an electrolyte, a cell, and a shell encapsulating the cell, the electrolyte is injected into the cell in the shell, and the cell includes a positive plate, a negative plate, and a separator between the positive plate and the negative plate. Among them, the cell can be a laminated cell, that is, the cell is formed by interleaving and stacking the positive plate, the separator and the negative plate; or the cell can also be a winding type cell, that is, the cell is formed by winding after stacking the positive plate, the separator and the negative plate.

[0091] Specifically, the positive plate includes a positive current collector and a positive active layer on at least one side surface of the positive current collector. Specifically, the positive active layer can be arranged on one side surface in the thickness direction of the positive current collector, or the positive active layer can be arranged on both opposite side surfaces in the thickness direction of the positive current collector.

[0092] Specifically, when the battery of the embodiment of the application is a lithium ion battery, the positive active layer can include a positive active material, a conductive agent and a binder. In the positive active layer, the mass percentage of the positive active material can be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 93%, 95%, 97%, 99% or a range composed of any two of them, the mass fraction of the conductive agent can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or a range composed of any two of them, and the mass fraction of the binder can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or a range composed of any two of them.

[0093] In some embodiments, the positive active material can include the above-mentioned positive active material, and a conventional lithium iron manganese phosphate positive active material can also be added to the positive active layer of the battery on the basis of using the above-mentioned positive active material.

[0094] In the embodiment of the application, the conductive agent in the positive active layer can be a conventional conductive material in the art, for example, the conductive agent in the positive active layer can include one or more of conductive carbon black, conductive graphite, carbon nanotubes (CNT), carbon fibers, graphene, acetylene black, and ketjen black.

[0095] In the embodiment of the application, the binder in the positive active layer can be a conventional binding material in the art, for example, the binder in the positive active layer can include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, oxirane-containing polymer, polyvinylpyrrolidone, polyurethane, etc.

[0096] The positive current collector of the present application can be a conventional positive current collector in the art, for example, the positive current collector comprises an aluminum foil.

[0097] In the present application, the coating, drying, rolling and other processes involved are conventional operations in the art, and the equipment used can be conventional equipment in the art, which is not particularly limited.

[0098] In the present application, the positive electrode sheet can be prepared by a conventional method in the art, for example, by a coating method. Specifically, the components for forming the positive active layer, such as the positive active material, the conductive agent, and the binder, can be dispersed in a solvent, such as N-methyl pyrrolidone (NMP), to prepare a positive electrode slurry, which is then coated on the surface of the positive current collector, and then subjected to drying, rolling and other processes to obtain the positive electrode sheet. The coating, drying, rolling and other processes involved are conventional operations for preparing the positive electrode sheet by the coating method, which is not particularly limited.

[0099] Specifically, the negative electrode sheet comprises a negative current collector and a negative active layer on at least one side surface of the negative current collector. Specifically, the negative active layer can be provided on one side surface of the negative current collector, or on both side surfaces of the negative current collector in the thickness direction.

[0100] Specifically, the negative active layer can comprise a negative active material, a conductive agent and a binder, which can all be conventional materials in the art. For example, the negative active material can comprise one or more of natural graphite, artificial graphite, petroleum coke, silicon-carbon material, the conductive agent can comprise one or more of conductive carbon black, carbon nanotube (CNT), acetylene black, graphene, ketjen black, carbon fiber, and the binder can comprise one or more of sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing an ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.

[0101] The negative current collector of the present application can be a conventional negative current collector in the art, for example, the negative current collector comprises a copper foil.

[0102] In the present application, the negative electrode sheet can be prepared by a conventional method in the art, for example, by a coating method. Specifically, the components for forming the negative active layer, such as the negative active material, the conductive agent, and the binder, can be dispersed in a solvent, such as water, to prepare a negative electrode slurry, which is then coated on the surface of the negative current collector, and then subjected to drying, rolling and other processes to obtain the negative electrode sheet. The coating, drying, rolling and other processes involved are conventional operations for preparing the negative electrode sheet by the coating method, which is not particularly limited.

[0103] The electrolyte of the embodiment of the present application can be a conventional electrolyte in the art, for example, the electrolyte is a non-aqueous electrolyte, which specifically can include an organic solvent, an additive and an electrolyte salt, the organic solvent for example includes one or more of ethylene carbonate (EC), diethyl carbonate (DEC) and propylene carbonate (PC), the additive for example includes fluoroethylene carbonate (FEC), the additive for example includes vinylene carbonate (VC), and the electrolyte salt can include a lithium salt, for example, lithium hexafluorophosphate (LiPF6) and the like, but is not limited thereto.

[0104] In the embodiment of the present application, the separator is used to separate the positive electrode sheet and the negative electrode sheet to avoid short circuit caused by contact between the positive electrode sheet and the negative electrode sheet, and the embodiment of the present application can use a conventional separator in the art, which is not particularly limited. For example, the separator material can be a separator made of one or more of high-density polyethylene, ultra-high-density polyethylene, low-density polyethylene, linear low-density polyethylene, high-density polypropylene, ultra-high-density polypropylene, polyimide and polyvinylidene fluoride.

[0105] In the embodiment of the present application, a conventional shell material in the art can be used to package the battery cell, and the shell for example includes an aluminum plastic film and other soft packaging materials, but is not limited thereto.

[0106] The embodiment of the present application can assemble the positive electrode sheet, the separator and the negative electrode sheet and other components into a battery through a conventional method in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet can be arranged in an interleaved and stacked manner to obtain a stacked battery cell (or a wound battery cell). Then, the battery cell is placed in a shell (outer package), and after conventional processes such as liquid injection (i.e. injection of electrolyte) and packaging, a battery is obtained.

[0107] The embodiment of the present application also provides a battery pack including the above-mentioned battery, which has advantages corresponding to the above-mentioned positive electrode active material, and details are not repeated.

[0108] Generally, the battery pack includes a plurality of the above-mentioned batteries, which are connected to form a battery pack as single batteries. The batteries can be electrically connected through a conventional method in the art, for example, in series, in parallel or in a mixed connection mode including both of the above-mentioned connection modes, which is not particularly limited.

[0109] The embodiment of the present application also provides a power consuming device including the above-mentioned battery or the above-mentioned battery pack, which has advantages corresponding to the above-mentioned positive electrode active material, and details are not repeated.

[0110] The power consumption equipment of the embodiment of the present application can be a conventional power consumption equipment in the field, for example, a power equipment (such as an electric vehicle, an electric automobile), an electronic equipment (such as a mobile phone, a tablet computer, a notebook computer, a digital camera, etc.), a wearable equipment (such as a watch, a bracelet, a VR glasses, etc.), an energy storage power station, etc., and is not particularly limited.

[0111] The technical solutions of the present application are further described below in combination with specific embodiments.

[0112] Embodiment 1

[0113] The positive electrode active material of the present embodiment is prepared by the following method:

[0114] 1) Dissolve lithium hydroxide (lithium source), phosphoric acid (phosphorus source), manganese sulfate (manganese source), ferrous sulfate (iron source), titanyl sulfate (M source), carbon nanotubes (carbon source), polyaniline (as a nitrogen source and a template control agent), and diethylene glycol (an organic dispersant) in water, then mix and ultrasonically stir for 20 min to obtain a mixed solution, then deliver the mixed solution into a stirring hydrothermal reaction kettle, seal and replace the atmosphere in the kettle with nitrogen, set the temperature rising rate of the hydrothermal reaction to 5 ℃ / min, the reaction temperature to 180 ℃, and the reaction time to 6 h; wherein the mass ratio of polyaniline to the carbon source is 2:1.

[0115] 2) After the reaction is completed, the product of the above hydrothermal reaction is subjected to solid-liquid separation by a centrifuge, then the solid component is washed with deionized water for 3 times, and the washed product is vacuum dried at 60 ℃ for 12 h to obtain a sub-micron positive electrode active material;

[0116] 3) The solid of the sub-micron positive electrode active material is ground and passed through a 200-mesh sieve, then sintered at a temperature of 700 ℃ and a temperature rising rate of 5 ℃ / min for 2 h under a nitrogen atmosphere to obtain a positive electrode active material.

[0117] The kernel composition (in the table as kernel), the number ratio of carbon atoms and nitrogen atoms in the shell layer (in the table as nitrogen / carbon ratio), the powder resistivity of the positive electrode active material, the particle size of the positive electrode active material (in the table as particle size), and the shell layer thickness of the present embodiment are shown in Table 1.

[0118] Embodiment 2

[0119] The present embodiment is basically the same as Embodiment 1, except that the present embodiment uses glucose:PEG=5:1 as the carbon source.

[0120] Embodiment 3

[0121] The present embodiment is basically the same as Embodiment 1, except that the present embodiment uses graphene as the carbon source, urea as the nitrogen source, and polystyrene as the template control agent, and the carbon source:nitrogen source:template control agent=1:1:1.

[0122] Examples 4-13 differ from Example 1 in that the mass ratio of lithium hydroxide (lithium source), phosphoric acid (phosphorus source), manganese sulfate (manganese source), ferrous sulfate (iron source), titanyl sulfate (M source), carbon nanotubes (carbon source), polyaniline (as nitrogen source and template control agent), diethylene glycol (organic dispersant) are different.

[0123] Example 14

[0124] This example differs from Example 1 in that step 3) of this example is to grind the above sub-micron positive electrode active material solid and pass through a 300 mesh screen, then sinter at a temperature of 700°C under a nitrogen atmosphere at a heating rate of 5°C / min for 2h to obtain a positive electrode active material.

[0125] Example 15

[0126] This example differs from Example 1 in that step 3) of this example is to grind the above sub-micron positive electrode active material solid and pass through a 100 mesh screen, then sinter at a temperature of 700°C under a nitrogen atmosphere at a heating rate of 5°C / min for 2h to obtain a positive electrode active material.

[0127] Example 16

[0128] This example differs from Example 1 in that step 3) of this example is to grind the above sub-micron positive electrode active material solid and pass through a 200 mesh screen, then sinter at a temperature of 600°C under a nitrogen atmosphere at a heating rate of 5°C / min for 2h to obtain a positive electrode active material.

[0129] Example 17

[0130] This example differs from Example 1 in that step 3) of this example is to grind the above sub-micron positive electrode active material solid and pass through a 200 mesh screen, then sinter at a temperature of 750°C under a nitrogen atmosphere at a heating rate of 5°C / min for 4h to obtain a positive electrode active material.

[0131] Example 18

[0132] This example differs from Example 1 in that step 3) of this example is to grind the above sub-micron positive electrode active material solid and pass through a 100 mesh screen, then sinter at a temperature of 500°C under a nitrogen atmosphere at a heating rate of 5°C / min for 1h to obtain a positive electrode active material.

[0133] Example 19

[0134] The difference between the present example and Example 1 is that the step 3) of the present example is to grind the above-mentioned sub-micron positive electrode active material solid and pass through a 100-mesh screen, then sinter at a temperature of 750°C under a nitrogen atmosphere at a temperature increasing rate of 5°C / min for 6h to obtain the positive electrode active material.

[0135] Example 20

[0136] The present example is basically the same as Example 1, except that the M source in step 1) of the present example is zinc sulfate.

[0137] Example 21

[0138] The present example is basically the same as Example 1, except that the M source in step 1) of the present example is magnesium sulfate.

[0139] Comparative Example 1

[0140] The present comparative example is basically the same as Example 1, except that the present comparative example does not add polyaniline, i.e., there is no nitrogen source and template control agent.

[0141] Comparative Example 2

[0142] The present comparative example is basically the same as Example 1, except that the present comparative example does not add titanyl sulfate (M source).

[0143] Comparative Example 3

[0144] The difference between the present comparative example and Example 1 is that the present comparative example does not perform step 3), and the sub-micron positive electrode active material obtained in step 2) is sintered with carbon nanotubes at a temperature of 700°C at a temperature increasing rate of 5°C / min for 2h (the air atmosphere is argon) to obtain the positive electrode active material. That is, the core of the positive electrode active material of the present comparative example is the same as that of Example 1, the shell layer contains nitrogen and carbon elements, and there is an interface between the core and the shell layer.

[0145]

[0146] Test Example

[0147] Positive electrode active material resistivity test: dry the positive electrode material powder in a vacuum oven at 80-120°C for 12 hours to remove water interference; remove large particles with a 200-400 mesh screen to ensure uniformity; fill the test cavity with the powder evenly (avoid accumulation or voids), and scrape the surface flat after filling; set a constant pressure of 30 MPa; start the test, the instrument automatically applies a small current and measures the voltage drop; record the resistance value (R) or directly read the resistivity; release the pressure, re-sample, repeat 3 times, and take the average value. The test results are shown in Table 1 (powder resistivity of positive electrode active material).

[0148] Battery performance test: 1) The positive active material in the examples and comparative examples was mixed with conductive carbon black, PVDF in a weight ratio of 96%:2%:2%, and a positive electrode slurry was obtained by dispersion. The slurry was coated on an aluminum foil current collector, and the positive electrode was prepared by rolling at a positive electrode area density of 4.12 g / cm 3 Rolling was performed, and a positive electrode sheet was prepared;

[0149] 2) Artificial graphite, styrene diene rubber (SBR), and carboxymethyl cellulose sodium, conductive carbon black were mixed in a weight ratio of 94%:3%:2%:1%, and the mixture was dispersed in water to obtain a negative electrode slurry by double planetary mixing. The slurry was coated on a copper current collector, and then rolling and drying were performed to obtain a negative electrode sheet;

[0150] 3) The positive electrode sheet, the negative electrode sheet, and the separator were assembled into a lithium ion battery, and a non-aqueous electrolyte was injected. The electrolyte was mixed in a mass ratio of ethylene carbonate (abbreviated as EC):diethyl carbonate (abbreviated as DEC):propylene carbonate (abbreviated as PC)=2:5:3, 5% of fluoroethylene carbonate (abbreviated as FEC) based on the total mass of the electrolyte was added, 13% of lithium hexafluorophosphate (abbreviated as LiPF6) based on the total mass of the electrolyte was added, and additives vinylene carbonate (abbreviated as VC, 1%), lithium difluoro(oxalato)borate (abbreviated as LiDFOB, 1%) were added, and the additive content accounted for 2% of the total content of the electrolyte.

[0151] Initial efficiency test: After the obtained batteries were placed at 25°C for 4h, the first charge-discharge capacity test was performed, and the test conditions were as follows: 0.2C charging to 4.55V, constant voltage charging to 0.025C cutoff, standing for 3min, 0.2C discharging to 3.0V, obtaining the charge-discharge curve, and recording the first charge capacity C0 (0.2C charge specific capacity in Table 2) and the first discharge capacity D0 (0.2C discharge specific capacity in Table 2) of 4.4-4.55V, respectively, and calculating the first coulombic efficiency (initial efficiency in Table 2) according to D0 / C0.

[0152] 1C cycle 300 cycle capacity retention rate test: The capacity retention rate / thickness change rate of the obtained batteries was tested, and the specific test method was as follows: at 25°C, charging to 4.50V at a charge rate of 1C, then charging to 4.50V at a charge rate of 0.05C, and then discharging to 3.0V at a discharge rate of 1C, repeating this charge-discharge cycle 300 times, measuring the discharge capacity Q1 at the first cycle and the discharge capacity Q 500 300 at the 300th cycle. The capacity retention rate Q after 300 cycles was calculated according to the following formula.

[0153] Capacity retention rate Q=Q 500 / Q1*100%, the results are shown in Table 2 (1C cycle 300 cycles capacity retention rate).

[0154] Battery total impedance test: the battery of the above examples and comparative examples is tested for battery total impedance using an electrochemical workstation (CHI760E). Specifically, the above battery is connected with the electrochemical workstation, positive electrode→working electrode (WE), negative electrode→counter electrode (CE) and reference electrode (RE); the working parameters are set, frequency range (100 kHz - 0.1 Hz), amplitude (10 mV) and the like; the test is run, the test data is fitted with an appropriate circuit model, and the ohmic resistance (R Ω ) and charge transfer resistance (R ct ) are read, and the battery total impedance = R Ω + R ct . The results are shown in Table 2 (battery total impedance).

[0155]

[0156] As can be seen from the table, compared with the comparative examples, the positive electrode active material of the embodiments of the application has good electron and ion conductivity and high stability when having the above structure, which is conducive to reducing the impedance of the battery and improving the capacity, first charge efficiency and capacity retention rate of the battery; compared with examples 2, 3 and 5, example 1 further controls the particle size of the positive electrode active material, thereby further reducing the impedance of the battery and better improving the capacity, first charge efficiency and capacity retention rate of the battery; compared with examples 8 and 9, example 1 further controls the number ratio of nitrogen atoms to carbon atoms in the shell, thereby better improving the capacity, first charge efficiency and capacity retention rate of the battery; compared with example 12, example 1 further controls the content of iron element in the positive electrode active material, thereby further reducing the impedance of the battery and better improving the capacity, first charge efficiency and capacity retention rate of the battery; compared with examples 18 and 19, example 1 further controls the thickness of the shell of the positive electrode active material, thereby further reducing the impedance of the battery and better improving the capacity, first charge efficiency and capacity retention rate of the battery.

[0157] Finally, it should be noted that: the above examples are only used to illustrate the technical solutions of the present application, but not to limit them; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that they can still modify the technical solutions described in the foregoing examples, or make equivalent substitutions for part or all of the technical features; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A positive electrode active material, characterized in that The positive electrode active material includes a core and a shell layer covering at least a portion of the surface of the core; The core includes LiMn 1-x Fe x M y PO4; Where 1-x>0; x>0; y>0; The M element includes one or more elements selected from the group consisting of Mg, Ca, Sr, Co, Ti, Zr, Ni, Cr, and Zn; The shell layer includes carbon elements and nitrogen elements.

2. The positive electrode active material according to claim 1, characterized in that The resistivity of the positive electrode active material is 10 Ω·cm to 100 Ω·cm.

3. The positive electrode active material according to claim 2, characterized in that In the kernel, 0.2≤x≤0.7; and / or, 0<y≤0.

02.

4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The particle size of the positive electrode active material is 0.2 μm to 0.6 μm; and / or, the thickness of the shell layer is 1 nm to 5 nm; And / or, the ratio of nitrogen atoms to carbon atoms in the shell is 0.01 at% to 0.1 at%.

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that The positive electrode active material is prepared using a method comprising the following steps: The raw materials including lithium source, manganese source, iron source, phosphorus source, M source, carbon source and nitrogen source are subjected to hydrothermal reaction and sintering treatment in sequence to obtain the positive electrode active material.

6. A method for preparing the positive electrode active material according to any one of claims 1 to 5, characterized in that: The steps include: The raw materials including lithium source, manganese source, iron source, phosphorus source, M source, carbon source and nitrogen source are subjected to hydrothermal reaction and sintering treatment in sequence to obtain the positive electrode active material.

7. The method for preparing a positive electrode active material according to claim 6, characterized in that: Before the hydrothermal reaction, the method further includes adding at least one of a template control agent and an organic dispersant to the raw material and then performing the hydrothermal reaction; Wherein, the template control agent includes one or more of polyaniline, dopamine, polystyrene, and polyvinyl alcohol; and / or, the organic dispersant comprises one or more of ethylene glycol, diethylene glycol, glycerol, and polyethylene glycol; And / or, the mass ratio of the template control agent to the carbon source is (0.5-2.5):1; And / or, the phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, sodium phosphate, and sodium dihydrogen phosphate; And / or, the manganese source includes one or more of manganese oxalate, manganese carbonate, manganese sulfate, and manganese acetate; And / or, the iron source includes one or more of ferric oxalate, ferric nitrate, and ferric sulfate; And / or, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, and lithium oxalate; and / or, the carbon source comprises one or more of graphene, carbon nanotubes, glucose, starch, ascorbic acid, and polyethylene glycol; And / or, the nitrogen source includes one or more of urea, imidazole, and polyaniline.

8. The method for preparing a positive electrode active material according to claim 6 or 7, characterized in that: The heating rate of the hydrothermal reaction is 2°C / min to 20°C / min; preferably, the heating rate of the hydrothermal reaction is 5°C / min to 15°C / min; And / or, the reaction temperature of the hydrothermal reaction is 100° C. to 200° C.; preferably, the reaction temperature of the hydrothermal reaction is 150° C. to 190° C.; And / or, the reaction time of the hydrothermal reaction is 3h~10h; preferably, the reaction time of the hydrothermal reaction is 4h~7h; And / or, the heating rate of the sintering process is 1°C / min to 10°C / min; preferably, the heating rate of the sintering process is 3°C / min to 6°C / min; And / or, the reaction temperature of the sintering treatment is 500° C. to 750° C.; preferably, the reaction temperature of the sintering treatment is 600° C. to 750° C.; And / or, the reaction time of the sintering treatment is 1 hour to 6 hours; preferably, the reaction time of the sintering treatment is 2 hours to 4 hours.

9. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode active layer, and the positive electrode active layer includes the positive electrode active material according to any one of claims 1 to 5 or the positive electrode active material prepared by the method for preparing the positive electrode active material according to any one of claims 6 to 8.

10. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Supercritical solvent thermal preparation method of cathode material lithium iron phosphate of lithium ion battery

    CN102790216A

  • Nitrogen-sulfur-co-doped surface modified lithium iron phosphate positive electrode material, preparation method and uses thereof

    CN107895778A

  • A nitrogen-doped carbon-coated lithium ferromanganese phosphate material n and a preparation method thereof-

    CN109244391A

  • Composite positive electrode material and preparation method and application thereof

    CN114335461A

  • Lithium manganese iron phosphate material as well as preparation method and application thereof

    CN117996020A

Cited By

  • Positive electrode active material and preparation method thereof, positive plate, battery, battery pack and electric equipment

    CN121662810A